PENDAMPINGAN PENERAPAN SISTEM PENGENDALIAN INTERNAL PERSEDIAAN PADA UMKM DISTRIBUTOR BUAH CV. ANEKA BUAH SEGAR - Putra, Kharisma Nugraha; Hidayati, Hidayati; Rahman, Rahman; Alexandro, Rinto; lenlioni, Liling (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
The internal control system for inventory is crucial to be implemented in every business unit, including MSMEs. This can be achieved through mentoring the implementation of the internal control system for inventory, such as in an MSME located in Palangka Raya city, CV. ABS. The purpose of this community service is to for inventory so that the partner's inventory management can operate effectively and efficiently. The activity was carried out from July to August 2024 at CV. ABS in Palangka Raya City. The stages of implementing the community service program included the preliminary stage, the preparation of the internal control system for inventory, the training stage, the simulation stage, and the monitoring stage. The result of this activity is that the partner experienced benefits such as increased knowledge, ranging from understanding the internal control system for inventory to the implementation of an effective and efficient internal control system. This includes having an organizational structure that separates functions and responsibilities, procedures for receiving and issuing inventory, and adequate document in inventory management